To Evaluate the Effect of Chronic Obstructive Pulmonary Disease on Retinal and Choroidal Thicknesses Measured by Optical Coherence Tomography. (8th October 2019) - Alim, Sait; Demir, Helin Deniz; Yilmaz, Ayşe; Demir, Selim; Güneş, Alper
Abstract : Purpose . To evaluate the retinal and choroidal thicknesses in patients with chronic obstructive pulmonary disease using optical coherence tomography. Methods . The study included 26 patients with chronic obstructive pulmonary disease (COPD) and 26 age-matched healthy control groups. Detailed ocular examinations were performed on all participants. Cirrus EDI-OCT (enhanced depth imaging-optical coherence tomography) was used for choroidal thickness measurements with frame enhancement software. The subfoveal area was used for choroidal thickness measurements. Results . The patients with the chronic obstructive pulmonary disease had an average 239.13 ± 57.77 μ m subfoveal choroidal thickness, and the control group had an average 285.02 ± 25 μ m subfoveal choroidal thickness. The subfoveal choroidal thickness measurements revealed a statistically significant difference between patients and the control group (p < 0.05 ). There were no statistically significant differences between patients and control group regarding mean macular thickness, central macular thickness, and GCIPL (ganglion cell-inner plexiform layer) thickness. Also, there was no statistically significant difference between patients and control group regarding mean, superior, nasal, inferior, and temporal RNFL (retinal nerve fiber layer) thicknesses. Conclusion . Chronic hypoxemia seems to cause decreased choroidal thickness in patients with chronic obstructive pulmonary disease.